A New Possibility for Fermentation Monitoring by Electrical Driven Sensing of Ultraviolet Light and Glucose - Amorim, Cleber A. [UNESP]; Blanco, Kate C.; Costa, Ivani M. [UNESP]; de Araújo, Estácio P.; do Nascimento Arantes, Adryelle; Contiero, Jonas [UNESP]; Chiquito, Adenilson J. (MDPI, 2020)
Industrial fermentation generates products through microbial growth associated with the consumption of substrates. The efficiency of industrial production of high commercial value microbial products such as ethanol from glucose (GLU) is dependent on bacterial contamination. Controlling the sugar conversion into products as well as the sterility of the fermentation process are objectives to be considered here by studying GLU and ultraviolet light (UV) sensors. In this work, we present two different approaches of SnO2 nanowires grown by the Vapor–Liquid–Solid (VLS) method. In the GLU sensor, we use SnO2 nanowires as active electrodes, while for the UV sensor, a nanowire film was built for detection. The results showed a wide range of GLU sensing and as well as a significant influence of UV in the electrical signal. The effect of a wide range of GLU concentrations on the responsiveness of the sensor through current–voltage based on SnO2 nanowire films under different concentration conditions ranging was verified from 1 to 1000 mmol. UV sensors show a typical amperometric response of SnO2 nanowires under the excitation of UV and GLU in ten cycles of 300 s with 1.0 V observing a stable and reliable amperometric response. GLU and UV sensors proved to have a promising potential for detection and to control the conversion of a substrate into a product by GLU control and decontamination by UV control in industrial fermentation systems.
Keywords: Controlling fermentation; Glucose sensor; Nanowire biosensor; UV light sensor